Does parietal cortex contribute to feature binding? - Ashbridge, E; Cowey, A; Wade, D (1999)
We studied the involvement of the right parietal cortex in visual conjunction search, where two features are present in the array and spatial attention and feature binding is required, and in subset search, where two features are also present but only one of them is needed in order to group stimuli together (the subset) and allow parallel processing without the need for feature binding. Six patients with right parietal lobe lesions, six age-matched controls, and three control patients with left parietal lesions were tested on these two tasks. Patients with right parietal lesions were significantly slower than normal controls in the conjunction task, especially for target-absent trials. In the subset condition, neither normal control subjects nor patients with left parietal damage showed a difference between target-present and target-absent trials whereas right parietal patients showed a significant difference between target-present and target-absent responses. The results suggest a role for the right parietal cortex in shifting attention to the next stimulus once binding of features has taken place or selecting spatial areas containing the desired feature in a subset search, but that parietal cortex is not required for binding the features of the object.